Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Essai français, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»--Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

Companion to sexuality studies - Naples, Nancy A. (Wiley-Blackwell companions to sociology, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

Le corps féminin malade comme hétérotopie queer : analyse des récits autopathographiques féministes lesbiens de Verena Stefan (D'ailleurs) et d'Audre Lorde (Journal du cancer et Un souffle de lumière) - Bélanger, Jennifer (Université du Québec à Montréal, 2019)
Ce mémoire s'intéresse aux lignes (de fuite et de risque) qui émergent du corps malade des narratrices et créent de nouvelles cartographies corporelles, des manières inédites d'être au monde. Son objectif est d'analyser la performance du corps féminin malade comme hétérotopie queer et les modalités d'inscription de la maladie dans les œuvres autopathographiques Journal du cancer (1980) et Un souffle de lumière (1988) d'Audre Lorde, et D'ailleurs de Verena Stefan (2008). Ces textes, chaotiques, offrent des représentations subjectives du cancer du sein et du foie, mais refusent de témoigner d'un quotidien qui serait uniquement marqué par l'expérience de la maladie. Ainsi, le récit du diagnostic et des traitements est entrelacé, chez Stefan, avec celui de son processus migratoire et, chez Lorde, avec celui de sa survivance en tant que poète lesbienne et noire née aux États-Unis. En s'écrivant, ces auteures défient les discours normatifs et dévoilent une construction discursive de soi qui met en œuvre un contrediscours. À l'intérieur de l'institution médicale, elles sont un site que l'on cherche à normaliser et à baliser; toutefois, leur corps narré, en refusant de vivre en ligne droite et de se réorienter, se définit comme un ailleurs, comme une hétérotopie, tant spatiale que sémantique. Ma démonstration se décline en trois chapitres : le premier sert à définir ce qu'est et ce que fait l'autopathographie en tant que registre narratif qui répond à l'impératif de jeter du sens sur un corps bruyant, tandis que les deux autres bâtissent une analyse croisée des œuvres. Le deuxième chapitre, en arrimant les réflexions de Michel Foucault sur les hétérotopies à celles de Sara Ahmed sur la phénoménologie queer, développe l'idée que les corps lesbiens malades des narratrices s'incarnent en « espaces autres», visibles et invisibles, lisibles et illisibles. Il est dès lors question des actes de lecture qui adviennent entre les narratrices et les spécialistes, lesquels dévoilent et réactualisent les signes inscrits (transcrits) sur et dans leur corps malade. J'y oppose deux postures, soit le face-à-face médical et le corps-à-corps amoureux, afin de mettre en lumière une approche qui puisse toucher et lire différemment ce corps souffrant. Finalement, le troisième chapitre s'attarde à ce qui, dans l'écriture des récits, se risque au cri comme symptôme d'un langage qui déborde. Le cri pointe à et vers autrui en contournant, tout en l'aiguisant, l'écart entre celle qui l'émet et celle qui l'accueille. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : hétérotopie, autopathographie, ligne de fuite, phénoménologie, patiente, médecin, corps malade, cancer, féminisme, femmes, queer, lesbiennes.
Keywords: IREF; approches et analyses; arts; corps; corps féminin; discipline; identités; lesbianisme; mémoires/thèses; queer; ressource en ligne; santé; thématiques; études littéraires

« A fairly typical boy », « a fairly typical girl » - Piccand, Laura (Emulations - Revue de sciences sociales, 2018)
Les stades dits de Tanner sont une série de photographies permettant d’évaluer le développement pubertaire des filles et des garçons. Utilisés dans la clinique et la recherche médicales contemporaines, leur histoire remonte aux années 1950. Cet article propose de revenir sur le contexte de production de cet artefact et d’interroger la façon dont il est partie prenante de la construction socio-historique de la binarité du sexe dit biologique. La puberté comme objet scientifique et médical est en effet un lieu crucial de production, de reproduction et de reconfiguration du genre.
Keywords: 1900-1999; 1950-1959; 1960-1969; angleterre; approches et analyses; cours; discipline; discours dominant; europe; inégalités; londres; patriarcat; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques

Les sujets intersexes peuvent-ils (se) penser ? - Charlebois, Janik Bastien (Socio, 2017)
Les personnes intersexuées sont rendues invisibles par les mythes sociaux sur l’hermaphrodisme et le troisième sexe. Pourtant, certaines d’entre elles se politisent afin de faire cesser les interventions non consensuelles que la médecine pratique sur elles dans le but de conformer leur corps aux normes « mâle » et « femelle ». Saisis de cette critique, les médecins s’investissant dans la prise en charge intersexe l’invalident partant du postulat que ces personnes qui prennent la parole dans l’espace public sont rares. Pour comprendre cette faible présence des perspectives intersexes critiques, nous mobilisons les concepts de subjectivation politique de Lamoureux (2001) et de Gaulejac (2007), de même que celui d’injustice épistémique de Fricker (2007). À partir de données empiriques et de savoirs construits sur le terrain par l’auteure à titre de chercheure engagée intersexe, cet article relève les mécanismes institutionnels encadrant les possibilités de construction d’une position de sujet réflexif, puis les composantes requises au développement d’une position d’acteur sujet.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; intersexuation; personnes intersexes; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; sciences humaines; sexualité; soc2014; soc3113; sociologie; systèmes d'oppressions; thématiques

Pour des interventions anti-oppressives auprès des jeunes trans: nécessités sociales, évidences scientifiques et recommandations issues de la pratique - Medico, Denise; Pullen-Sansfaçon, Annie (Service social, 2017)
Depuis 2011, de plus en plus d’études documentent les besoins et enjeux des jeunes et des enfants qui se sentent différent.e.s dans leur genre. S’il en ressort qu’illes sont encore parmi les jeunes les plus à risque de suicide, de violence par les pairs, d’échec scolaire, de dépression, d’anxiété et de troubles alimentaires, un milieu de vie qui les accepte et les soutient semble le facteur le plus déterminant pour leur santé tant psychique que relationnelle et somatique et leur insertion sociale et professionnelle. Pour favoriser un développement harmonieux pour les jeunes trans et en questionnement, une perspective anti-oppressive est aujourd’hui nécessaire.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; transféminisme; travail social; trs1205; violences

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (Collection Logiques sociales. Série Sociologie du genre, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Hormones et reconfiguration des identités sexuelles au Brésil - Sanabria, Emilia (Clio. Femmes, Genre, Histoire, 2013)
Les hormones sexuelles sont des objets hybrides et complexes à la frontière du sexe et du genre. Dès lors qu’elles sont synthétisées sous forme pharmaceutique, elles peuvent attribuer des caractéristiques sexuelles au corps de manière partiellement exogène à celui-ci. Il s’en suit que l’utilisation clinique qui en est faite est socialement réglementée. À travers une analyse de divers contextes d’utilisation des hormones observés à Bahia, au Brésil, cet article montre que le dualisme sexuel est le produit de pratiques de régulation biomédicales qui visent à encadrer la circulation des hormones. Le sens du terme local « hormônio » n’est pas pleinement recoupé par celui d’hormone, qu’il excède. L’emploi commun qui est fait au Brésil du singulier procure au terme « hormônio » une qualité fluide et homogène. Dans ce contexte, les hormones sont comprises comme une sorte de substance qui peut circuler entre les corps. Cette conceptualisation des hormones comme une substance a des implications pour le statut ontologique des corps et révèle la relative plasticité de la relation sexe/genre.
Keywords: 1900-1999; 1950-1959; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du sud; amériques; approches et analyses; brésil; corps; cours; discipline; discours dominant; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

Mon corps a-t-il un sexe? Détermination du sexe et contraintes du genre. - Guillot, Vincent (Identités intersexes: identités en débat, 2013)
L'Observatoire des transidentités (O.D.T.) est une interface de visibilité des questions trans, militantes comme universitaires. Dans cet ouvrage, les responsables de l'O.D.T. ont restitué des débats, des textes et des rencontres autour des questions transidentitaires (classifications médicales, dépsychiatrisation, mouvements LGBTIQ, films et reportages, Trans and Queer studies, etc.).. Les contributeurs de ce livre, qu'ils soient chercheurs ou militants, proposent des éléments de représentations dépathologisants autour des transidentités et une réflexion transdisciplinaire sur les multiples formes que prennent aujourd'hui les identités de genre. Ce second volume porte son attention sur la question intersexe et sur le(s) communautés LGBT.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

United in anger: a history of ACT UP - Hubbard, Jim; Schulman, Sarah; ACT UP Oral History Project; United in Anger, Inc (United in Anger, Inc., 2012)
"A unique feature-length documentary that combines startling archival footage that puts the audience on the ground with the activists and the remarkably insightful interviews from the ACT UP Oral History Project to explore ACT UP (the AIDS Coalition to Unleash Power) from a grassroots perspective - how a small group of men and women of all races and classes, came together to change the world and save each other's lives."
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; act up; amériques; approches et analyses; cinéma; communication; cours; discipline; documentaire; film; intersectionnalité; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; soc2014; thématiques; états-unis

Les pratiques féminismes - Institut de recherches et d'études féministes (FéminÉtudes, 2012)
Ce numéro de 2012 illustre les pratiques féministes entre engagements, luttes et théories. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; féminétudes; genre; identités LGBTQIA2+; intersectionnalité; intervention féministe; périodes historiques; queer; québec; ressource en ligne; régions géographiques; santé; santé mentale; sexualité; thématiques

Queer Bioethic: Why its Time Has Come. - Wahlert, Lance; Fiester, Autumn (Bioethics, 2012)
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; care; corps; cours; discipline; identités LGBTQIA2+; lit4700; premier cycle; queer; ressource en ligne; santé; sciences; thématiques; éthique

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Le bouclier thérapeutique: discours et limites d’un appareil de légitimation - Espineira, Karine (Le sujet dans la cité, 2011)
En 1982, le professeur René Küss plaide à la télévision pour un protocole appelant à distinguer entre « vrais » et « faux » trans’ : de « vrais trans’ » ne causent aucun trouble dans le genre : on leur accorde une aide exceptionnelle (l’opération) par laquelle - hommes devenus femmes ou femmes devenues hommes - ils rentrent dans l’ordre du genre et de l’identité. Telle est l’une des premières expressions de ce que nous proposons d’appeler le « bouclier thérapeutique ». Les trois décennies qui suivent voient s’affronter les affirmations transidentaires et l’idéologie dominante des « traitants ». Appareil de légitimation d’un ordre ancien, le « bouclier thérapeutique » ne serait-il plus aujourd’hui pour ses partisans que le dernier vestige d’une ère marquée par l’effritement d’un deuxième bouclier, juridique celui-ci, garantissant que la libre disposition de l’état civil reste une exception ? Sur ces questions qui interrogent profondément les représentations que nos sociétés se font d’elles-mêmes, peut-être le temps est-il venu d’ouvrir la route tracée par la recherche en sciences sociales et humaines aux nouveaux paradigmes amorcés par les Études de Genre.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; care; cours; discipline; discours; europe; france; inégalités; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; transféminisme; violences; violences institutionnelles; violences médicales

Transidentité: de la théorie à la politique. Une métamorphose culturelle entre pragmatisme et transcendance - Espineira, Karine (L'information psychiatrique, 2011)
Du décret français du 10 février 2010 aux travaux de réécriture lancés par le DSM et la CIM, les questions transidentitaires doivent être discutées, appréhendées sur le plan théorique aussi bien que politique. Le schisme entre les associations d’usagers, les trans’ en demande et/ou en obligation de suivi, et les équipes hospitalières spécialisées dans la prise en charge de ce public, pour le cas de la France tout particulièrement, a une histoire intimement liée à un ordre présumé du social et de ses acteurs en termes de genre dans une vision binaire de la société. La demande de reconnaissance de savoirs, d’expertises du terrain transidentitaire s’est heurtée, dès le début des années 1980, au bouclier thérapeutique , que l’on peut définir comme l’argument ultime de l’instance médico-légale en charge du sujet transsexe, écartant les autres sujets/trajets trans’, pour mettre à distance toute intervention du politique, des sciences humaines et sociales dans ce qui est devenu un paradigme théorique : le changement de sexe est d’abord un changement culturel de genre. Enfin, l’instance médico-légale s’efforce d’ignorer sa propre politisation et militance. Partagé entre la volonté de résister et de participer face/avec un protocole inadapté, inefficace et culturellement obsolète, le terrain a connu ses propres mouvements s’interrogeant, s’interpellant sur l’esprit de la méthode. La question trans’ compte désormais autant de politiques que de groupes. La théorisation du fait trans’, trouve sa légitimité non pour revenir seulement sur l’inégalité homme/femme, mais pour lutter du même élan contre toute forme d’inégalité et de stigmatisation. Le terrain transidentitaire s’est profondément transformé, les outils pour l’appréhender comme le paradigme théorique lui-même, se doivent une chose : évoluer.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; militance; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; sociologie; thématiques; transféminisme; violences; violences médicales

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social

Critical intersex - Holmes, Morgan (Queer interventions, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Pushing the limits disabled dykes produce culture - Tremain, Shelley (Women's Press, 2009)
Cet impressionnant recueil de prose, de poésie, de chansons et d'art visuel rédigé par des lesbiennes handicapées est la première de deux anthologies liées (la seconde est un recueil d'essais). Dans son introduction percutante (« Nous sommes ici. Nous sommes handicapés et queer. Habituez-vous-y »), la rédactrice en chef Shelley Tremain appelle à la reconnaissance et à la compréhension du monde selon les lesbiennes handicapées. La collection elle-même est colérique, compatissante, drôle et surtout émouvante. Sherree Clark présente des extraits de son recueil de poésie et d'art Living with Arthritis. Margot K. Lane célèbre la sexualité dans un merveilleux poème intitulé « Full day ». Le récit posthume de Kathleen Martindale sur le cancer du sein est un appel à l’action contre le personnel médical insensible, tout comme la chronique de Kathleen Rockhill sur sa guérison d’un accident de voiture dévastateur. Combinant colère et célébration, Pushing the Limits est une révélation.
Keywords: amériques; anthologie; approches et analyses; arts; canada; capacitisme; corps; lesbianisme; littérature; outils; ouvrages de références; patriarcat; personnes lesbiennes; poésie; queer; racisme; ressource en ligne; régions géographiques; santé; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sport et bicatégorisation par sexe : test de féminité et ambiguïtés du discours médical - Bohuon, Anaïs (Nouvelles Questions Féministes, 2008)
Dès les années 30, des sportives font l’objet d’un procès de virilisation dans des épreuves d’athlétisme en raison de morphologies jugées trop « masculines ». Ces athlètes se rapprochent des hommes non seulement par le physique, mais aussi par leurs performances. Des soupçons sont alors émis quant au sexe des sportives. En 1966, un test de féminité est instauré par le monde médical sportif afin de contrôler le sexe des concurrentes et s’assurer que celles-ci ne bénéficient pas d’avantages physiques que les femmes ne sont pas censées posséder. Notre article consiste à montrer les ambiguïtés des discours médicaux face aux controverses soulevées par le test de féminité qui, dévoilant les niveaux pluridimensionnels de l’identité sexuée, obligent le milieu médico-sportif à s’interroger sur la définition d’une « vraie femme ».
Keywords: 1900-1999; 1930-1939; 1960-1969; approches et analyses; cours; discipline; discours dominant; europe; france; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; sport; systèmes d'oppressions; thématiques

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (Cultural front, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

An archive of feelings: Trauma, sexuality, and lesbian public cultures - Cvetkovich, Ann (Series Q, 2003)
Dans ce nouvel ouvrage audacieux de critique culturelle, Ann Cvetkovich développe une approche queer du traumatisme. Elle défend l’importance de reconnaître – et d’archiver – les récits de traumatismes qui appartiennent autant à l’ordinaire et au quotidien qu’au domaine de la catastrophe. An Archive of Feelings soutient que le domaine des études sur le traumatisme, limité par une division trop stricte entre le public et le privé, a négligé les expériences des femmes et des queers. Rejetant les conceptions pathologisantes du traumatisme qui imprègnent les discours médicaux et cliniques sur le sujet, Cvetkovich développe plutôt une approche sexuellement positive qui manque même dans la plupart des travaux féministes sur le traumatisme. Elle met le domaine au défi de s’intéresser plus pleinement au traumatisme sexuel et au large éventail de sentiments qui l’entourent, y compris ceux associés au sexe butch-femme et à l’activisme et à la prise en charge du sida. An Archive of Feelings rassemble les histoires orales de militantes lesbiennes impliquées dans Act Up/New York ; lectures littéraires de Dorothy Allison, Leslie Feinberg, Cherríe Moraga et Shani Mootoo ; vidéos de Jean Carlomusto et Pratibha Parmar ; et des performances de Lisa Kron, Carmelita Tropicana et des groupes Le Tigre et Tribe 8. Cvetkovich révèle comment l'activisme, la performance et la littérature donnent naissance à des cultures publiques qui fonctionnent à travers le traumatisme et transforment les conditions qui le produisent. En examinant de près les liens entre la sexualité, le traumatisme et la création de cultures publiques lesbiennes, Cvetkovich fait de ces expériences qui ont été reléguées à la périphérie de la culture du traumatisme les principes déterminants d'une nouvelle construction du traumatisme sexuel, une construction dans laquelle le traumatisme catalyse la création. des archives culturelles et des communautés politiques.
Keywords: amériques; approches et analyses; hétérosexisme; lesbianisme; militance; personnes lesbiennes; queer; régions géographiques; santé; systèmes d'oppressions; thématiques; violences; états-unis

Intersexe et transsexualités : Les technologies de la médecine et la séparation du sexe biologique du sexe social - Löwy, Ilana (Cahiers du Genre, 2003)
Le sexe social est construit sur un mode binaire. Par contre, le sexe biologique se présente comme un continuum, avec, aux deux extrêmes, les « sexes biologiques » clairement définis et, au milieu, une large gamme de situations intermédiaires — des individus « intersexe ». De tels individus remettent en cause nos certitudes sur la stabilité des catégories « homme » et « femme ». Cet article trace l’histoire des interventions médicales ayant pour but de corriger l’anomalie de l’intersexe et de produire des êtres humains dont le corps ne remet pas en cause la bipolarité du féminin et du masculin. Il suit les débats sur les liens supposés entre intersexualité et homosexualité puis expose la transition du traitement de l’intersexualité à celui de la transsexualité. Il étudie enfin le rôle des nouvelles techniques de la médecine dans la séparation entre le « sexe » et le « genre ». La possibilité de moduler les paramètres du « sexe biologique » permet alors une réflexion sur le « sexe social » comme variable indépendante des structures biologiques.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (Des hommes et des femmes en changement, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Invisible lives the erasure of transsexual and transgendered people - Namaste, Viviane K. (University of Chicago Press, 2000)
Invisible Lives est la première étude scientifique sur les personnes transgenres – travestis, drag queens et transsexuels – et sur leur vie quotidienne. À travers une étude théorique et empirique combinée, Viviane K. Namaste soutient que les personnes transgenres ne sont pas tant produites par la médecine ou la psychiatrie qu'elles sont effacées ., ou rendu invisible, dans une variété de contextes institutionnels et culturels. Namaste commence son travail en analysant deux perspectives théoriques sur les personnes transgenres - la théorie queer et les sciences sociales - montrant comment aucune d'entre elles n'a abordé de manière adéquate les problèmes les plus pertinents pour le changement de sexe : tout, de l'emploi aux soins de santé en passant par les papiers d'identité. Namaste examine ensuite certaines des inscriptions rhétoriques et sémiotiques des figures transgenres dans la culture, y compris des études sur les premières sous-cultures punk et glam rock, pour illustrer comment l'effacement des personnes transgenres est organisé dans différents sites culturels. Invisible Lives se termine par de nouvelles recherches sur certaines des préoccupations quotidiennes des personnes transgenres, proposant des études de cas sur la violence, les soins de santé, les cliniques d'identité de genre et la loi.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discours dominant; fem1000; identités LGBTQIA2+; personnes trans*; premier cycle; queer; santé; sexualité; systèmes d'oppressions; thématiques; théories féministes; vie quotidienne; violences; études culturelles